2012
DOI: 10.1097/yct.0b013e31823a4220
|View full text |Cite
|
Sign up to set email alerts
|

A Within-Subject Comparison of Propofol and Methohexital Anesthesia for Electroconvulsive Therapy

Abstract: We recommend methohexital as the induction agent of choice for ECT, especially with right unilateral placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 17 publications
2
12
0
1
Order By: Relevance
“…They concluded that the strong antidepressive effect of ECT would overlap the ketamine effect, which could also be the case in the present study. 21,51 S-ketamine here was given in combination with propofol, which may weaken the possible S-ketamine effect. 34 It has been suggested that S-ketamine is twice as potent as racemic ketamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the strong antidepressive effect of ECT would overlap the ketamine effect, which could also be the case in the present study. 21,51 S-ketamine here was given in combination with propofol, which may weaken the possible S-ketamine effect. 34 It has been suggested that S-ketamine is twice as potent as racemic ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Usually intravenous doses between 1 and 2 mg/kg are used for inducing anesthesia. 21 Propofol relieves the psychotomimetic adverse effects of ketamine, and propofolketamine combination may be useful in ECT anesthesia. S(+) ketamine has been found to be a potent and effective anesthetic with less psychotomimetic adverse effects than racemic ketamine.…”
mentioning
confidence: 99%
“…Propofol was also associated with a significantly higher requirement for bilateral ECT and higher stimulus dosing. Seizure duration was significantly shorter in the propofol condition, with more patients requiring re-stimulation for brief seizures [11]. In another study Sackeim et al showed that increasing the electrical dosage increases the efficacy in patients receiving right unilateral ECT [12], which is known to have less cognitive side effects compared to bilateral stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Dado los efectos depresores cardiovasculares conocidos del propofol, reduce la respuesta hemodinámica aguda durante la TEC 42 . Vaidya et al muestran que el propofol, en comparación con methohexital, no afecta la mejoría en los síntomas depresivos, la duración de la estadía hospitalaria ni la recuperación cognitiva, sin embargo, en terapia con electrodo unilateral los pacientes que recibieron propofol necesitaron más sesiones de TEC que los que recibieron methohexital y en los pacientes con terapia con dos electrodos requirieron dosis mayores de inducción y estímulos eléctricos más altos 43 . La eficacia comparable con la droga estándar, su corta vida media, el despertar placentero de los pacientes y su efecto antiemético la hacen la droga de elección en TEC ambulatoria en nuestro país.…”
Section: -Vasodilatadores De Acción Directa: El Uso Deunclassified